Tötungsdelikte in Japan aus kriminalistischer, kriminologischer und rechtspolitischer Sicht - Ida, Makoto (Zeitschrift für Japanisches Recht, 2006)
Criminal statistics in Japan have shown a significant rise in violent crimes within the past ten years. However, the number of homicides committed has remained low. The number of suicides, on the other hand, is twenty times higher than the number of intentional homicides. Based on these facts, this article looks at aspects of homicide in Japan from the perspective of criminology, criminalistics, and law and legal policy. In 2004 the prescribed minimum period of imprisonment in a case of homicide (Art. 199 Criminal Code) was raised from three to five years. This was based on the consideration that the prescribed minimum and maximum period of imprisonment reflects the value attached to the respective interest protected. Because human life is a highly valued good, suspension of a sentence should only be possible in special extenuating circumstances. Also, the minimum period of imprisonment should not be lower for homicide than for robbery. The number of homicides committed per 100,000 inhabitants remained the same during the past ten years. Looking at the past 50 years, the number of homicides in Japan has declined considerably. The number of youthful offenders is very low. Generally speaking, the age of the offenders is rising, which can only partly be ascribed to the fact that Japanese society as a whole is aging. The age of the victims is also mounting. The majority of crimes are committed within the offender’s social circle. Although the number of homicides committed has not increased, sentences have become tougher. Sentences are also suspended less frequently and the death penalty is imposed more often. One reason given for this contradictory development is the fact that homicides have become more cruel and appalling in the way they are committed. On the other hand, the past ten years have seen a pronounced change in the public’s attitude toward criminal law. The media as well as politicians have launched heavy criticism on Japan’s criminal justice, making the latter responsible for rising crime rates. This criticism has led to several law reforms which have increased the maximum periods of imprisonment and promoted the protection of the victims. Japanese criminal law is now undergoing a fundamental change: Solutions are sought on a case-by-case approach. While this allows for a flexible adjustment to societal changes, systematic coherence is lost. The increase in robberies and other violent crimes has to be viewed in the light of the persisting economic crisis. Citizens have proven not to be immune to the temptation of crime. However, norms are internalized to such a degree that they deter from killing others. The present situation has to be seen as a temporary, economy-related phenomenon. Thus, caution is called for when implementing fundamental reforms and making deep invasions in criminal law. (The Editors)